Informator / "Solidarność" Region Środkowo-Wschodni . no. 173, 1989 - "Solidarność" Region Środkowo-Wschodni ([s.n.], 1989)
Creation and circulation: Publication contains listing of titles of Polish underground press, mostly from Środkowo-Wschodni region